Modeling a successful innovation ecosystem toward a sustainable community: The I-Reef (a review study) - Sedigheh Asefi; David Nunes Resende; Marlene Amorim (Energy Reports, 2020)
So far, numerous studies have exhibited Silicon Valley and other thriving innovation ecosystems by distinguishing special characteristics in which their survival rely on sustaining activities that convert them to specific regions. These regions provide ready-made grounds for networking to be innovative. Meantime, it is struggling for innovations to be transformed into measurable economic results if players encounter a weak network of collaborative relationships in the ecosystem. Besides, flowing back the created value in the same region could be another problem with the actual innovation ecosystems to be utilized by all players created this. It is interesting that successful innovation ecosystems share many characteristics with coral reefs in which the process of economic growth and the renewal of an evergreen region is credible in specific collaborative relationships. Hence, the I-Reef model suggests a particular ecosystem where All-Win contribution relationships of the regional innovation networks return the results into the whole region.
Keywords: 330; Sustainability; Innovation Reef; Win-All collaboration